2008
DOI: 10.1017/s0003598x00096836
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Pleistocene to mid-Holocene occupation and an early cremation burial at Ille Cave, Palawan, Philippines

Abstract: Excavations at a cave site on the island of Palawan in the Philippines show occupation from c. 11000 BP. A fine assemblage of tools and faunal remains shows the reliance of hunter-foragers switching from deer to pig. In 9500-9000 BP, a human cremation burial in a container was emplaced, the earliest yet known in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 28 publications
(23 reference statements)
1
39
0
Order By: Relevance
“…The fossils from Tabon and Callao document some of the earliest arrivals of the genus Homo in the Philippine archipelago, but late Upper Pleistocene and early Holocene human remains are almost absent from the Philippine fossil record. Until now, the cremated human remains recovered from Ille Cave (Palawan) and directly dated to ~9,000-9,500 cal BP are the only exception (Lewis et al 2008b). This finding documents the earliest intentional cremation from Southeast Asia, with a series of complex mortuary gestures before and after the cremation of the human bones (Lewis et al 2008b).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The fossils from Tabon and Callao document some of the earliest arrivals of the genus Homo in the Philippine archipelago, but late Upper Pleistocene and early Holocene human remains are almost absent from the Philippine fossil record. Until now, the cremated human remains recovered from Ille Cave (Palawan) and directly dated to ~9,000-9,500 cal BP are the only exception (Lewis et al 2008b). This finding documents the earliest intentional cremation from Southeast Asia, with a series of complex mortuary gestures before and after the cremation of the human bones (Lewis et al 2008b).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Until now, the cremated human remains recovered from Ille Cave (Palawan) and directly dated to ~9,000-9,500 cal BP are the only exception (Lewis et al 2008b). This finding documents the earliest intentional cremation from Southeast Asia, with a series of complex mortuary gestures before and after the cremation of the human bones (Lewis et al 2008b). The bones represent a female individual with a short stature (Lewis et al 2008b), and it is expected that future detailed morphological descriptions and comparisons could provide valuable insights on its biological affinities.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…A similar pattern of increased cave frequentation and magnitude of habitation at the end of the Pleistocene has been recorded at Niah , at Song Terus (Sémah and Sémah 2012) and Song Gupuh (Morwood et terra australis 45 al. 2008) in Java and at Ille Cave on Palawan (Lewis et al 2008). It has been argued that this reflects the movement of human populations inland from coastlines as the marine incursion disrupted ecological systems and reduced resource predictability (Piper and Rabett 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for the increasing use of pounders, grindstones and pestles and mortars for plant processing and grinding resins and minerals such as haematite across SEA in the early Holocene (Bellwood 1997: 181;Rabett et al 2013;Simanjuntak 2002 Lewis et al 2008). Close examination of bone surfaces indicated that this individual had been de-fleshed, dismembered and the long bones shattered prior to being burnt.…”
Section: Discussionmentioning
confidence: 99%
“…Other sites include Sumatra (van Heekeren 1972), Sarawak , Vietnam (Szabó unpublished data), and the Philippines (Fox 1970;Vitales 2009a), ranging from 10,000 years to as recently as 500 years ago. 2), is a multi-phase site, with evidence of cave utilisation ranging from periods as early as the terminal Pleistocene to as late as the 18 th century (Lewis et al 2006;Lewis et al 2008;UP-ASP 2005. A majority of the materials investigated in this paper come from a shell midden deposit, with associated artefacts from the Neolithic and Metal Ages, such as decorated and undecorated pottery, polished stone adzes, and various worked shells.…”
Section: Terra Australis 39mentioning
confidence: 99%